Exogenous silicon promotes cadmium (Cd) accumulation in Sedum alfredii Hance by enhancing Cd uptake and alleviating Cd toxicity - Hu, Ying; Zhou, Xueqi; Shi, An; Yu, Yanshuang; Rensing, Christopher; Zhang, Taoxiang; Xing, Shihe; Yang, Wenhao (Frontiers in Plant Science, 2023)
Silicon (Si) plays key roles in alleviating Cadmium (Cd) toxicity in plants. However, the effects of Si on mitigation of Cd toxicity and accumulation of Cd by hyperaccumulators are largely unknown. This study was conducted to investigate the effect of Si on Cd accumulation and the physiological characteristics of Cd hyperaccumulator Sedum alfredii Hance under Cd stress. Results showed that, exogenous Si application promoted the biomass, Cd translocation and concentration of S. alfredii, which lead to significantly increases in Cd accumulation by 412.39-621.00%. Moreover, Si alleviated Cd toxicity by: (i) increasing chlorophyll contents, (ii) improving antioxidant enzymes, (iii) enhancing cell wall components (lignin, cellulose, hemicellulose and pectin), (iv) raising the secretion of organic acids (oxalic acid, tartaric acid and L-malic acid). The RT-PCR analysis of genes that involved in Cd detoxification showed that the expression of SaNramp3, SaNramp6, SaHMA2 and SaHMA4 in roots were significantly decreased in the Si treatments, while Si significantly increased the expression of SaCAD. These results suggested that Si enhanced Cd resistance and facilitated the Cd phytoextraction of S. alfredii. This study expanded understanding on the role of Si in phytoextraction and provided a feasible strategy for assisting phytoextraction Cd by S. alfredii.